State of the art of the evaluation of public policy on territorialenvironmental planning in Colombia - Garcia-Cabana, Andrea Carolina (Revista Geográfica de América Central., 2021)
The evaluation of public policies has posed different challenges that seek to improve the performance of public management to achieve this it does so through the systematic measurement of the operation or impact of public programs or policies, which when compared with implicit or explicit standards allows to contribute to their improvement (Weiss, 1998). This article reviews the state of the literature, regarding the evaluation of public policies for environmental territorial planning in Colombia. A methodical review was made of the articles published in journals indexed in the databases SciELO.org and EBSCO Information Services in the period between 1995 and 2020. As a result of the research, the state of the art of the evaluation of public policies on the specific issue of territorial environmental planning in Colombia was obtained, and some recommendations were established to strengthen the dissemination of the public policy evaluation processes in the country